2007
DOI: 10.1002/cncr.23018
|View full text |Cite
|
Sign up to set email alerts
|

PEG‐IFN‐α‐2b therapy in BCR‐ABL–negative myeloproliferative disorders

Abstract: BACKGROUND.Interferon‐alpha (IFN‐α) has shown significant activity in the treatment of BCR‐ABL–negative myeloproliferative disorders (MPDs), particularly essential thrombocythemia (ET) and polycythemia vera (PV). PEG‐IFN‐α‐2b is a pegylated IFN‐α‐2b with a significant advantage over nonpegylated form in that it is administered once a week.METHODS.Thirty‐eight patients with BCR‐ABL–negative MPDs were treated with PEG‐IFN‐α‐2b, given subcutaneously weekly, at the starting dose of 3 μg/kg/wk for the first 14 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 47 publications
2
62
0
2
Order By: Relevance
“…Both standard and pegylated preparations of interferon-alpha appear to have little clinical effect in reducing splenomegaly and, as a result, their use is not recommended (Tefferi et al, 2001a;Jabbour et al, 2007;Ianotto et al, 2009). They do, however, have a role as myelosuppressive agents (see 'Myelosuppression Therapy' section).…”
Section: Splenomegaly and Extramedullary Haemopoiesismentioning
confidence: 99%
See 1 more Smart Citation
“…Both standard and pegylated preparations of interferon-alpha appear to have little clinical effect in reducing splenomegaly and, as a result, their use is not recommended (Tefferi et al, 2001a;Jabbour et al, 2007;Ianotto et al, 2009). They do, however, have a role as myelosuppressive agents (see 'Myelosuppression Therapy' section).…”
Section: Splenomegaly and Extramedullary Haemopoiesismentioning
confidence: 99%
“…In view of the particularly high rates of toxicity in PMF, the use of IFN in MPNs has been mainly restricted to PV and ET. Nevertheless, a number of studies of IFN in MF have been reported, although they give highly heterogeneous results, a fact complicated by non-standardized reporting of responses and lack of randomized control trial data (Gilbert, 1998;Tefferi et al, 2001a;Radin et al, 2003;Jabbour et al, 2007;Ianotto et al, 2009;Silver & Vandris, 2009). More recently, two small, retrospective, observational studies have shown more promising results in PMF patients.…”
Section: A-interferon (Ifn-a)mentioning
confidence: 99%
“…9 Recent studies have underscored the therapeutic value of pegylated IFN-a in CML 81 and other myeloproliferative neoplasms (polycythemia vera, essential thrombocythemia and primary myelofibrosis). [81][82][83][84][85][86] Preliminary data are available on its clinical use in AML; a recent case study by our group has illustrated the therapeutic potential of pegylated IFN-a in the setting of AML. 15 This was demonstrated by the induction of a long-lasting complete remission in a poor-prognosis AML superimposed on a preceding state of primary myelofibrosis.…”
mentioning
confidence: 99%
“…More recent reports have indicated that IFN-a is most frequently used in myelofibrotic patients (Kiladjian et al, 2008a). However, the use of Peg-IFN (a-2b) was reported only once and was found to produce poor results, with only one patient out of 11 achieving a 'complete response' (Jabbour et al, 2007). In a recent report, Peg-IFN a-2a induced haematological and even molecular responses in polycythaemic patients (Kiladjian et al, 2008b).…”
Section: Peg-ifn-a-2a Therapy In Patients With Myelofibrosis a Study mentioning
confidence: 99%